Perbedaan Pola Asuh Orang Tua Terhadap Kemandirian Anak - Umairoh, Siti; Ichsan, Ichsan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2018)
This research is motivated by an interest in the independence of group A children at RA Averous Bogoran Trirenggo Bantul. This study aims to determine the independence of group A children, parental tendencies, and differences in parenting parents towards the independence of group A children in RA Averous Bogoran Trirenggo Bantul. This type of research is quantitative research. The variables in this study include the variable parenting (Independent) and independence variable (Dependent). Respondents in this study were 34 children and parents from group A at RA Averous Bogoran Trirenggo Bantul. The results of the study in Aorous RA Bogoran Trirenggo Bantul group A obtained the results of the average independence of children in the low category of 5.88%, independence with the medium category as much as 26.48% and independence with a high category of 67.64%. For the authoritarian parenting trend of 11.77%, liberal parenting was 8.82%, and democratic parenting was 79.41%. Based on the results of statistical calculations using one way ANOVA test obtained F 45,393 with a significance value of 0,000 (0,000 <0,05), indicating that there are differences in parenting parents towards independence.